Boosting hydrogen production of uniform CuCo-ZIF nanododecahedrons by bimetal node and glycerol. (March 2023) - Wang, Q.; Ruan, W.; Teng, Y.; Ma, B.; Zhang, X.; Yuan, X.; Li, Z.; Jiang, W.; Teng, F.; Ibhadon, A.O.
Abstract: Compared with fossil fuels reforming to hydrogen, electrolytic water to hydrogen is highly energy-intensive. It is still a big challenge to decrease the cost of electrolytic water to hydrogen. Herein, we investigate the electrocatalytic activity of uniform bimetal zeolite imidazole framework (Cux Coy -ZIFs, x : y = 1:3, 1:1, 3:1 mol ratio) nanododecahedrons. Bimetal Cux Coy -ZIFs show an obviously higher oxygen evolution reaction (OER) activity than ZIF-67, which is mainly attributed to the synergistic effect of Co and Cu. The Cu doping accelerates electron transfer and optimizes the electron structure of Co. In addition, the in-situ generated hydroxides/oxides (Co(OH)2, Cu(OH)2 Co3 O4, Cu2 O) during electrocatalytic reaction may be the main active sites are for ZIF-67 and Cux Coy -ZIF. Meanwhile, density functional theory calculations demonstrate that H + and OH − adsorptions on Cu1 Co1 -ZIF are more favorable thermodynamically than that on ZIF-67. Furthermore, when OER is substituted by glycerol oxidation reaction (GOR), the anodic GOR current increases by 8.9 times than OER current. Compared with OER-based electrolyzer, the cell voltage of GOR-based electrolyzer has decreased by 18.81%, and its Faradaic efficiency rises to 94.4%. The innovative system can efficiently produce hydrogen at an ultra-low electric energy consumption and a high conversion of energy. Graphical abstract: Cu x Co y -ZIF with Bimetal nodes exhibits an obviously superior HER and OER activities to ZIF-67 because of the improved adsorption and electron transfer ability. To produce the same H2 amount, 18.81% electric energy is economized for GOR electrolyzer, compared to OER one. Image 1 Highlights: The introduction of Cu greatly improved adsorption and electron transfer ability. Bimetal Cu1 Co1 -ZIF showed an obviously higher OER activity than ZIF-67. HER efficiency was greatly boosted by the substitution of GOR for OER. 18.81% of electric energy is economized for GOR electrolyzer, compared to OER one.